2019
DOI: 10.1186/s12889-019-6859-1
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and psychological distress of employees across socioeconomic strata: a cross-sectional study

Abstract: Background 1Little is known of the extent of workplace bullying in Malaysia, despite its growing recognition worldwide as a serious public health issue in the workplace. Workplace bullying is linked to stress-related health issues, as well as socioeconomic consequences which may include absenteeism due to sick days and unemployment. We sought to examine the prevalence of workplace bullying and its association with socioeconomic factors and psychological distress in a large observational study of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
4
33
1
Order By: Relevance
“…Our findings were also different from the majority of studies—workers with low and minimum-wage were more likely to be bullied [ 1 , 46 , 47 ] because their employment is often at the will of the employers. Our finding was consistent with a Malaysian study [ 48 ] and Chan and colleagues argued that income levels may not be a clear indicator for risk of workplace bullying even where economic disparities are evident. In the context of Hong Kong, it is likely that those with higher monthly income occupy a better and hierarchically higher position in their workplace.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were also different from the majority of studies—workers with low and minimum-wage were more likely to be bullied [ 1 , 46 , 47 ] because their employment is often at the will of the employers. Our finding was consistent with a Malaysian study [ 48 ] and Chan and colleagues argued that income levels may not be a clear indicator for risk of workplace bullying even where economic disparities are evident. In the context of Hong Kong, it is likely that those with higher monthly income occupy a better and hierarchically higher position in their workplace.…”
Section: Discussionsupporting
confidence: 92%
“… 48 , 57 , 58 Such vulnerability to bullying among junior staff could be caused by collapsed coping mechanisms for workplace stressors or the hierarchical structure within the organization that demands work beyond one’s capabilities while trying to adapt to a new organizational climate. 24 , 59 Similarly, workers who were not involved in patient care, such as administrative or clerical staff, were highly vulnerable to workplace bullying, and this finding was consistent with a previous study. 33 …”
Section: Discussionsupporting
confidence: 90%
“…From the Malaysian perspective, studies have attempted to explore bullying in the workplace in the non-healthcare 24,25 and health-care domains. [26][27][28] These works have provided useful insights to further explore the magnitude of workplace bullying, particularly from health workers' perspectives, given the escalated burden faced in modern medical practice for greater commitment to service delivery and organizational structure.…”
Section: Introductionmentioning
confidence: 99%
“…This was lower than that reported in 'Pregnancy and Maternity-Related Discrimination and Disadvantage: Experiences of Mothers', published by the government of the UK, in which 20% of mothers experienced harassment or negative comments related to pregnancy or flexible working from their employer and/or colleagues. 34 Chan et al 10 reported that gender-based workplace bullying is experienced by nearly 40% of general female employees. However, our study showed that one-third of those who felt harassment eventually resigned from work, which was much higher than the 17.1% resignation rate in female workers in a general population in 2018.…”
Section: Discussionmentioning
confidence: 99%